Effectiveness and safety of percutaneous endoscopic debridement and drainage for spinal infections: a systematic review and meta-analysis - Guozhong Zhou; Xiaorong Liu; Zhi Liang; Xuesong Chen; Chao Song (Journal of Orthopaedic Surgery and Research)
Abstract Background Spinal infections (SI) typically manifest with and pose a growing medical challenge. However, current evidence for treating SI is limited and inconclusive. Our aim was to assess the effectiveness and safety of percutaneous endoscopic disc decompression (PEDD) for SI. Methods On 20 October 2023, we searched the EMBASE, PubMed, Cochrane Library, China Biology Medicine Disc, China National Knowledge Infrastructure, and Wanfang databases for eligible studies. Cohort studies on SI treated with PEDD, reporting relevant effectiveness or safety outcomes. We assessed study quality using a modified Newcastle–Ottawa Scale and conducted a random-effects meta-analysis to calculate pooled results. Results Overall, 36 studies involving 925 patients were included. Erythrocyte sedimentation rate levels decreased significantly at 1-week postoperatively compared with preoperative levels (mean difference [MD] = − 13.48 [95% CI − 15.65 to − 11.31]) and continued to decrease over 3 months. Similarly, the c-reactive protein (CRP), visual analogue scale, and oswestry disability index scores significantly reduced postoperatively. The rates of excellent or good MacNab classification were 92.6% (95% CI 84.1–98.1%). Microbiological diagnostics revealed a 71.7% (95% CI 65.5–77.6%) positive rate in tissue cultures, surpassing blood cultures (odds ratio [OR] 2.72 [95% CI 1.01–7.30]). The rates of complication, reoperation, and mortality were 4.1% (95% CI 1.5–8.0%), 8.6% (95% CI 4.3–14.3%), and 1.7% (95% CI 0.4–4.1%), respectively. Subgroup analyses demonstrated a significantly lower reoperation rate in the group that discontinued antibiotics based on a normal CRP than in the fixed-duration group (2.7% [95% CI 0.3–7.7%] vs 20.1% [95% CI 14.5–26.3%], p = 0.0002). Conversely, ambulation 1 day postoperatively was associated with a higher reoperation rate than ambulation within 5–14 days (16.2% [95% CI 9.3–24.6%] vs 1.1% [95% CI 0.0–6.0%], p = 0.0060). Conclusion Our meta-analysis suggests that PEDD is a potentially effective and safe intervention for SI. Optimizing antibiotic discontinuation and postoperative care strategies may contribute to reducing reoperation rate. However, these findings require further validation from controlled studies.